2007
DOI: 10.1007/s00127-007-0255-3
|View full text |Cite
|
Sign up to set email alerts
|

Household roles, poverty and psychological distress in internally displaced persons affected by violent conflicts in Indonesia

Abstract: Different risk factors were identified for each household role of IDP, indicating that their mental health care requirements may be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
(39 reference statements)
0
23
0
4
Order By: Relevance
“…From the international literature, the expulsion event has been variously set off by combat, killings, arrests, maltreatment, forced labor, torture, sexual violence, kidnapping, ethnic violence, and human rights abuses [5766, 67•, 71, 77, 79, 80, 82, 90]. Expulsion frequently results in separation from family members and acute shortages of survival resources such as food and shelter [78, 79, 83, 91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the international literature, the expulsion event has been variously set off by combat, killings, arrests, maltreatment, forced labor, torture, sexual violence, kidnapping, ethnic violence, and human rights abuses [5766, 67•, 71, 77, 79, 80, 82, 90]. Expulsion frequently results in separation from family members and acute shortages of survival resources such as food and shelter [78, 79, 83, 91].…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon the locale and the conflict situation, IDPs experience impoverished living conditions characterized by overcrowding, lack of privacy, shared beds, exposure to animals and insect vectors, insecurity and vulnerability to violence, and scarcity of basic needs including nutritious food, drinking water, sanitation, and health care [5760, 63, 64, 70, 72, 74, 75, 90]. Documented mental health problems associated with long-term resettlement include PTSD, depression, PTSD-depression comorbid diagnosis, generalized anxiety disorder, panic disorder, somatoform disorder, somatic complaints, alcoholism, sleep disturbances, emotional reactivity, psychological distress, elevated suicide risk, perceived stigmatization, helplessness and guilt after witnessing violence, and long-term disability associated with mental health problems [3, 4••, 5, 6, 5762, 67•, 68••, 69, 70, 7375, 79, 82, 100].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of mental health in conflict and post-conflict situations have reported high rates of psychopathology among IDP populations [14, 10, 16, 2123]. A substantial proportion of the populations exposed to mass violence and conflict develop a variety of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off point from the instrument that measures anxiety symptoms on this study is 1.75 (score range from 0 -4.00) (Strand, Dalgard, Tambs, & Rognerud, 2003) This instrument has been widely used in different countries. As previous studies in similar Asian population found 1.75 to be appropriate (Turnip & Hauff, 2007), therefore this study also adopted this cutoff point in this studyThus, participants' anxiety mean score on this study is considered as high (M = > 1.75). Meanwhile, teacher expectation score mean on this study is deemed to be low because usually based on previous researches that used the same instrument, for example, Tyler and Boetler (2008), have mean score on point 3.00 or specifically 3.88 or 4.00 (score range from 0 -4.50).…”
Section: Resultsmentioning
confidence: 99%
“…ESA-Related Teacher Practices translated into Bahasa Indonesia through back translation and expert judgment process with coefficient alpha 0.836. This study used ten first items of The Hopkins Symptom Checklist (HSCL) -25 that has been translated into Bahasa Indonesia by Turnip and Hauff (2007) to adopt cultural and language issues. Coefficient alpha of 10 first items HSCL-25 is 0.84 (Derogatis et al, 1974).…”
Section: Instrument and Measurement Related Teachermentioning
confidence: 99%